Empirical Analysis of MSCI China A-Shares - Yan Li (MDPI AG, 2021)
In this paper, we introduce the MSCI China A-shares index (MCASI) and analyze MCASI’s properties. From the perspective of index investment, we found that MCASI’s investor sentiments, both overnight sentiment and BW sentiment, provide significant predictability for future MCASI returns, supported by the in-sample and out-of-sample results. From the perspective of sector investment, we show that the sector portfolio of “information transfer, software and information technology services” performs the best among the 10 sector portfolios. In addition, seven approaches of the optimal portfolio in ten sectors are examined, and the results suggest that the classic Markowitz portfolio approach is recommended. Our empirical analysis is helpful for domestic and foreign investors seeking to form investment strategies for MSCI China A-shares.